Scalable and integrated flow synthesis of triple-responsive nano-motors via microfluidic Pickering emulsification. (December 2020) - Kaang, Byung Kwon; Mestre, Rafael; Kang, Dong-Chang; Sánchez, Samuel; Kim, Dong-Pyo
Highlights: Microfluidic Pickering emulsification shows improved Pickering efficiency, reproducibility. Integrated flow strategy enables a scalable manufacturing production of the multi-functional nano-motors. Triple-responsive nano-motor shows synergetic movement by H2 O2, NIR and magnet. Triple-responsive nano-motors can function for water-purification. Abstract: Artificial micro-/nano-motors are tiny machines as newly emerging tools capable of achieving numerous tasks. In principle, the self-phoretic motions require asymmetric structures in geometry and chemistry. However, conventional production techniques suffered from complex and time consuming multi-step process in low uniformity, and difficult to endow multi-functions into motors. This work disclosed a continuous-flow synthesis of triple-responsive (thermophoretic, chemical and magnetic movement) nano-motors (m-SiO2 /Fe3 O4 -Pdop/Pt) via microfluidic Pickering emulsification in a process of integrated and scalable manner. The droplet microfluidic process allows efficient self-assembly of the silica nanoparticles surrounding the spherical interface of resin droplet, rendering excellent Pickering efficiency and reproducibility, and followed by anisotropic decoration of polydopamine (Pdop) and Pt catalyst in a serial flow process. The obtained Janus nanoparticles reveal double- or triple-responsive self-propulsions with synergic mobility by combining thermophoresis powered by light, catalytic driven motion in H2 O2 or magnetic movement by magnet. Further, a non-metallic polydopamine based thermophoretic motion as well as an automated nano-cleaner for rapid water purification by dye removal are convincingly functioned. Finally, this novel integrated flow strategy proves a scalable manufacturing production (> 0.7 g hr −1 ) of the nano-motors using inexpensive single microreactor, fulfilling quantitative and qualitative needs for versatile applications. Graphical abstract: Nano-motor Synthesis of via Microfluidic Pickering Emulsification enables a scalable production of triple-responsive nano-motors with high uniformity and reproducibility, which allows the movement of (i) thermophoresis powered by near‐infrared (NIR) light, (ii) catalytic decomposition of hydrogen peroxide (H2 O2 ) and (iii) magnetic movement by external magnet. Image, graphical abstract